2012
DOI: 10.1590/s1516-35982012000200027
|View full text |Cite
|
Sign up to set email alerts
|

Performance, carcass characteristics and non-carcass components of Texel × Santa Inês lambs fed fat sources and monensin

Abstract: -Performance, carcass, non-carcass and commercial cuts and components of Texel × Santa Inês crossbred lambs, managed in confinement and fed diets based on soybean oil, soybeans and a conventional diet, with or without the use of monensin (78 ppm dry matter basis) were evaluated. Thirty-six Texel × Santa Inês lambs (18 males and 18 females) were managed in intensive systems. Animals were slaughtered after 87 days of confinement, and performance, carcass characteristics, weight and percentages of carcass and non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 24 publications
3
5
1
2
Order By: Relevance
“…REA superiority in Dorper cross animals suggests that these animals produce more muscle under the same conditions of feeding and management and, therefore, may produce more meat. Mean CCI was 0.24, similar to the values reported by Soares et al (2012) in cross Santa Inês x Texel sheep, and superior to the indices found for cross¾ Boer x ¼ Saanen (GRANDE et al, 2009) goats, which reached a mean of 0.20, both confined, fed different sources of fat, and slaughtered with 30kg. The same authors found a mean of 0.28 for LCI, values that are very inferior to the mean observed for goats (0.50), shown in Table 2.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…REA superiority in Dorper cross animals suggests that these animals produce more muscle under the same conditions of feeding and management and, therefore, may produce more meat. Mean CCI was 0.24, similar to the values reported by Soares et al (2012) in cross Santa Inês x Texel sheep, and superior to the indices found for cross¾ Boer x ¼ Saanen (GRANDE et al, 2009) goats, which reached a mean of 0.20, both confined, fed different sources of fat, and slaughtered with 30kg. The same authors found a mean of 0.28 for LCI, values that are very inferior to the mean observed for goats (0.50), shown in Table 2.…”
Section: Resultssupporting
confidence: 79%
“…This difference may be related to the age, body weight at slaughter, and goat breed used. CCI translates the deposition of muscle and fat per unit of carcass length and, therefore, the comparison between the results of the present study and those of Soares et al (2012) and Grande et al (2009) enabled the conclusion that, for this index, there is no difference between animals finished in confinement or in pastures, supplemented with mineral protein mix. WML values in MB sheep and cross Dorper animals were 1734.63 g and 1896.23g, respectively, which were greater than the values of all treatments in the study by Santos et al (2011), who evaluated the muscularity and adiposity of the carcass in Santa Inês lambs finished in confinement and recorded WML values of 1615.50; 1664.70; 1659.80; and 1554.10g, for animals treated with different levels of palm meal (0; 33; 66, and 100%) replacing ground corn, and slaughtered with 35kg.…”
Section: Resultssupporting
confidence: 54%
“…Dávila-Ramírez et al [ 10 ] reported similar results in body weight gain, feed intake, and feed efficiency with 6% soybean oil. Others with 2% [ 36 ] or 3% [ 11 ] soybean did not find a response in lamb performance, even when methane emission was reduced in this last study. In one experiment, when Crescentia alata and Guazuma ulmifolia fruits were offered ad libitum, the intake of Crescentia alata was minimal (48 g/d) compared to the Guazuma ulmifolia fruit (686 g/d), which severely affected daily gain in lambs (81 versus 4 g/d) [ 14 ].…”
Section: Resultscontrasting
confidence: 53%
“…Entretanto, de acordo com Soares et al (2012), a perna apresenta valores mais elevados em fêmeas. Neste trabalho os resultados estão de acordo com os da literatura, sendo que machos apresentam maiores porcentagens de paleta (CUNHA et al, 2000;SIQUEIRA;FERNANDES, 2001).…”
Section: Methodsunclassified
“…Outros pesquisadores (CUNHA et al, 2000(CUNHA et al, , 2001 também obtiveram diferenças na espessura de gordura subcutânea mas não na área de olho de lombo. Por outro lado, Soares et al (2012) não obtiveram diferença na espessura de gordura subcutânea em animais machos e fêmeas.…”
Section: Methodsunclassified